Satellite Attitude Control Using Control Moment Gyroscopes - Kenedy Matiasso Portella; Wilcker Neuwald Schinestzki; Róger Mateus Sehnem; Leonardo Barros da Luz; Lorenzzo Quevedo Mantovani; Renan Rathis Sacco; Tarso Kraemer Sarzi Sartori; Pedro Paglione (Journal of Aerospace Technology and Management, 2020)
In space missions, there is often a need for an attitude control system capable of maintaining the desired attitude. In situations that require agile and accurate responses, which also require large torques, control moment gyroscopes (CMGs) may be used. Control moment gyroscopes are high angular moment gyros mounted on gimbals and are responsible for changing the direction of the angular momentum vector, consequently generating the control torques. There are several linear and nonlinear techniques that can be employed in the design of control laws with the final choice being a compromise between simplicity, effectiveness, efficiency and robustness. The main objective of this study is to evaluate the performance of control systems techniques with 4 CMGs in a pyramidal arrangement, either by using Linear Quadratic Tracker (LQT) with integral compensator or Exponential Mapping Control (EMC). A reference attitude will be defined to be traced in the presence of disturbance torques caused by the gravitational gradient.